2010
DOI: 10.3390/d2040572
|View full text |Cite
|
Sign up to set email alerts
|

cTBP: A Successful Intron Length Polymorphism (ILP)-Based Genotyping Method Targeted to Well Defined Experimental Needs

Abstract: There seem to be a certain degree of reluctance in accepting ILP-based methods as part of the range of molecular markers that are classically used for plant genotyping. Indeed, since DNA polymorphism results from difference in length of fragments amplified from specific gene loci, not anonymous sequences, the number of markers that can be generated is sometime inadequate for classical phylogeny studies. Yet, ILP-based markers have many other useful advantages that should not go neglected. We support this state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
4

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 35 publications
0
13
0
4
Order By: Relevance
“…We have not isolated and cloned the fragments amplified from Ae. biuncialis , since the previous sequence study of amplicons obtained by h‐TBP method from different plants revealed that each amplified band corresponded to a specific β‐tubulin isotype (Bardini et al, ; Breviario et al, ; Braglia et al, , Galasso et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We have not isolated and cloned the fragments amplified from Ae. biuncialis , since the previous sequence study of amplicons obtained by h‐TBP method from different plants revealed that each amplified band corresponded to a specific β‐tubulin isotype (Bardini et al, ; Breviario et al, ; Braglia et al, , Galasso et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…The length of Ae. biuncialis amplified fragments were always longer than 300 bp, what corresponds to the location of primer pairs within the coding sequence (Breviario et al, ; Braglia et al, ). The fragments longer then 1000–1200 bp for TBP analysis and 2000 bp for h‐TBP analysis are reproducible and are involved in differentiation of hetero‐ and/or homoduplex DNA populations, what may be a possible explanation for these high‐molecular fragments formation during the amplification.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…В той же час, як джерело ДНК-поліморфізму все більшої популярності набувають інтрони. Встановлено, що інтрони беруть участь у численних важливих молекулярних подіях -контролі експресії генів через механізм альтернативного сплайсингу та інших процесах [15][16][17][18][19]. Еволюція екзонних і інтронних послідовностей йде з різною швидкістю [20,21], при цьому інтрони є гіперваріабельними ділянками, і можуть мати різний нуклеотидний склад і довжину, навіть у межах однієї таксономічної одиниці.…”
unclassified